PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MACTH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 22 DURI BARAT KECAMATAN MANDAU - Dewi, Sustra; Hamizi, Hamizi; Erlisnawati, Erlisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abtract:This Research was done, students at the fifth grade of SDN 22 Duri was low ability in science social because teacher always used advice method and did not have a variety model in learning process. so that, students difficult to understand , students cannot focus on their study, student, Teacher did not practice to students in learning process. From the explanation above, the researcher is interested in carrying out a research entitled “using cooperative tipe make a match at the fifth grade or sdn 22 duri”.This research purpose to improve the result of students in science social at the fifth grade of SDN 22 Duri. The class of fifth grade was 30 students, 13 for woman and 17 foman .this research was done with 2 cycle, every cycle have 2 meeting with 1 daily exam. Instrument the data for this research is observation and test. The result of the data activity teacher and students in cycle I for first meetingwas 75 %, improve in second meeting became 87.5% and in cycle II for first meeting more improve became 91.67% and for second meeting 95.83%. Thenactivity students in cycle I for first meeting reduced 70.83% improve in second meeting reduced became 79.17%. at the first test, there was no students could achieve this level at the first test 87.5 %, but at the second test was 95.83%..From the result of data this research was improve students with base score 64.5 in cycle I became 76.3 with the percentage 18.29% and improve in cycle II was 85.5 with percentage 32.6%. test well done in base score was 12 students (40%), that improve in cycle I became 22 students (73%), and more improve in cycle II became 26 students (87%). After conducting this study, the researcher realized that using cooperative tipe make match in learning process can improve the result of science social study students at the fifth grade of SDN 22 Duri Barat Kecamatan Mandau.Key words : Cooperative tipe make a match, study result.